Biaxial orientation optical polyester film

By adopting biaxially oriented optical polyester film and using the acid modification principle of modified polyester, the problems of bubble generation and high cost in the polyester film during the peeling process are solved, and the effect of easy peeling, low cost and excellent performance is achieved.

CN119682360AActive Publication Date: 2025-03-25HEFEI LUCKY SCIENCE & TECHNOLOGY INDUSTRY COMPANY LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411877020.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Existing polyester films are prone to bubbles during peeling, which affects the appearance of PPF self-repairing surfaces, and has high cost or poor performance.

Method used

Biaxially oriented optical polyester film is adopted, and three-layer structures of A/B/A or A/B/C are coextruded. The A and C layers contain modified polyesters. The modified polyesters are obtained by copolymerizing dibasic acid and diols to ensure the stability and performance of the modified polyesters.

Benefits of technology

It realizes easy peeling of polyester film, simple process and low cost, and does not affect the contact angle and brightness of the surface water of PPF self-repairing surface, avoiding the occurrence of orange peel patterns.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005197446970000171
    Figure BDA0005197446970000171
Patent Text Reader

Abstract

The invention relates to a biaxial orientation film, in particular to a biaxial orientation optical polyester film which is co-extruded by adopting an A / B / A or A / B / C three-layer structure, and the A layer and the C layer contain modified polyester; the modified polyester is obtained by copolymerizing binary acid and dihydric alcohol; the dibasic acid is 4-(3, 5-dicarboxyl phenoxy) phthalic acid, 2-(carboxyl methoxy)-4-fluorobenzoic acid, 4, 4-propane diradical dioxy dibenzoic acid and terephthalic acid. The optical polyester film has the advantages of no influence on a water contact angle of a PPF self-repairing surface before and after stripping, no orange peel, easiness in stripping, simple process, low cost and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a biaxially oriented film, in particular to a biaxially oriented optical polyester film. Background Art

[0002] In the field of polymer materials, polyethylene terephthalate, which is formed by the esterification and polycondensation of terephthalic acid and ethylene glycol, has many excellent properties and can be used in different fields, such as spinning, engineering plastics, films, etc. BOPET film is made by melt co-extrusion and biaxial stretching of polyethylene terephthalate material; due to its good mechanical properties, thermal properties, electrical insulation and optical properties, it is widely used in packaging, industry, electrical, electronic, display, protection and other fields.

[0003] The automobile industry is developing rapidly, especially in recent years, new energy vehicles have made significant progress, and cars have become people's basic means of transportation. How to better protect the car paint has become the focus of attention of car owners. Car cover (PPF, paint protection film) plays an important role in protecting car paint. The main material of car cover, the most original one is PVC material, that is, polyvinyl chloride, which has low cost, but it is easy to yellow and crack over time. With the development of technology, due to its high temperature resistance, low temperature resistance, mildew resistance, sufficient elasticity and other characteristics, most of the current invisible car cover materials are TPU materials.

[0004] The overall structure of the car cover includes a white matte release film, an acrylic adhesive layer, a TPU carrier, a self-repairing layer, and an optical polyester film for self-repairing surface protection.

[0005] There are two mainstream types of car covers, which are mainly distinguished by their self-repairing functions, namely hydrophobic and hydrophilic. The main difference between the two lies in the water contact angle. Specifically, hydrophobic car covers refer to rainwater falling on the car cover and rolling down in balls; hydrophilic car covers refer to rainwater falling on the car cover and spreading out and sliding down in parallel. Since water droplets are easily formed on the surface of hydrophobic car covers, the formation of water droplets has two main effects. First, when exposed to sunlight, it acts as a convex lens and easily burns the car paint. Second, after the water droplets are dried, they are easy to leave water stains on the car body. Hydrophilic car covers do not have such disadvantages and are widely welcomed by car owners.

[0006] The optical polyester film used to protect the PPF self-repairing surface has the following main requirements: first, it does not affect the water contact angle of the PPF self-repairing surface before and after peeling; second, it does not affect the brightness of the PPF self-repairing surface before and after peeling; third, it is easy to peel off and there should be no jamming problems during the peeling process.

[0007] In view of the requirements of optical polyester film for PPF self-repairing surface protection, the existing technical solutions to solve the problem in the field of polyester film are: 1. Silicone oil or non-silicone release layer processing on the surface of polyester film to achieve easy peeling. 2. Anti-scratch coating treatment on the surface of polyester film to achieve a smooth surface of the film. 3. Use optical polyester film substrate with untreated surface, which is low cost.

[0008] Although technicians have conducted a lot of research on polyester film, the existing technical solutions to the polyester film problem still have many shortcomings: 1. Silicone oil or non-silicone release layer processing on the polyester film surface can achieve the purpose of small impact on the water contact angle before and after peeling; however, due to the release force on its surface, after being bonded with the PPF self-repairing surface, bubbles are easily generated during placement, and it peels off by itself, affecting the appearance of PPF; at the same time, when the silicone oil is released, the silicon in the release layer is easy to migrate to the self-repairing layer, affecting the effect of the self-repairing layer. 2. Although the surface of the polyester film is treated with an anti-scratch coating to achieve a smooth surface of the film and not affect the brightness of the PPF surface after peeling, it is easy to cause peeling jams due to its too flat surface, and the manufacturing cost is high. 3. The use of untreated optical polyester film substrates is low in cost, but the unevenness of the substrate surface (such as orange peel texture) is easily transferred to the PPF self-repairing surface. After peeling, the water contact angle of the hydrophilic self-repairing surface increases, the hydrophilic performance deteriorates, and the brightness of the PPF surface is also affected. Summary of the invention

[0009] The invention provides a biaxially oriented optical polyester film, which has the advantages of not affecting the water contact angle of a PPF self-repairing surface before and after peeling, having no orange peel pattern, being easy to peel, having a simple process, and having low cost.

[0010] In order to achieve the above technical purpose, the technical solution adopted by the present application is: a biaxially oriented optical polyester film, co-extruded with a three-layer structure of A / B / A or A / B / C, wherein the A layer and the C layer contain modified polyester;

[0011] The modified polyester is obtained by copolymerizing a dibasic acid and a diol;

[0012] Wherein, the dibasic acid is 4-(3,5-dicarboxyphenoxy)phthalic acid, 2-(carboxymethoxy)-4-fluorobenzoic acid, 4,4-propanediyldioxydibenzoic acid and terephthalic acid;

[0013] Definition: X1 is the content ratio of 4-(3,5-dicarboxyphenoxy)phthalic acid component relative to the total dicarboxylic acid components in the modified polyester;

[0014] X2 is the content ratio of 2-(carboxymethoxy)-4-fluorobenzoic acid component relative to the total dicarboxylic acid components in the modified polyester;

[0015] X3 is the content ratio of 4,4-propanediyldioxydibenzoic acid component relative to the total dicarboxylic acid components in the modified polyester;

[0016] X4 is the content ratio of the terephthalic acid component to the total dicarboxylic acid components in the modified polyester;

[0017] Among them, X1, X2, X3, and X4 satisfy the following relationship:

[0018] 5 mol%≤X1≤15 mol%

[0019] 2 mol%≤X2≤10 mol%

[0020] 3 mol%≤X3≤25 mol%

[0021] 50 mol%≤X4≤90 mol%

[0022] X1+X2+X3+X4=100 mol%.

[0023] As an improved technical solution of the present application, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid component in the modified polyester relative to the total dicarboxylic acid components is 7 mol %≤X1≤12 mol %.

[0024] As an improved technical solution of the present application, the content of 2-(carboxymethoxy)-4-fluorobenzoic acid component in the modified polyester relative to the total dicarboxylic acid components is 3 mol %≤X2≤9 mol %.

[0025] As an improved technical solution of the present application, the content of 4,4-propanediyldioxydibenzoic acid component in the modified polyester relative to the total dicarboxylic acid components is 5 mol %≤X3≤20 mol %.

[0026] As an improved technical solution of the present application, the diol is selected from one or more of ethylene glycol, propylene glycol, butanediol, 1,4-cyclohexanedimethanol, hexanediol, and polyethylene oxide glycol; the molar ratio of the dibasic acid to the diol is 1:1.21 to 1:1.46.

[0027] As an improved technical solution of the present application, the dibasic acid and the diol are copolymerized under a catalyst, and the catalyst is selected from antimony, iron, aluminum, germanium or titanium catalysts, and the addition amount is 80ppm to 300ppm.

[0028] As an improved technical solution of the present application, the dibasic acid and the diol are copolymerized in the presence of a stabilizer, the stabilizer being selected from trimethyl phosphate, triethyl phosphate, triphenyl phosphate, tri-n-butyl phosphate, tetrabutyl titanate, or tetraethyl titanate; the added amount is 25ppm to 130ppm.

[0029] As an improved technical solution of the present application, the optical polyester film has a thickness of 19 μm to 150 μm.

[0030] As an improved technical solution of the present application, the biaxially oriented optical polyester film structure is a three-layer A / B / A, and the thickness ratio of the A layer to the B layer is 1:16 to 1:5.

[0031] As an improved technical solution of the present application, the optical polyester film structure is a three-layer A / B / C, the thickness ratio of layer A to layer B is 1:35 to 1:10, the thickness ratio of layer C to layer B is 1:35 to 1:10, and the thickness of layer A and layer C can be the same or different.

[0032] Beneficial Effects

[0033] 1. The present invention utilizes the acid modification principle and starts from a microscopic perspective to modify the polyester polymer chain segments (by copolymerization, characteristic functional groups in new monomers such as phenoxy, methoxy, phenylfluoride, and dioxy groups are introduced into the modified polyester), thereby giving the polyester polymer materials brand-new properties and improving the added value of its deep-processing products.

[0034] 2. The present invention designs polyester polymer chain segments (the second and third monomers such as 4-(3,5-dicarboxyphenoxy)phthalic acid, 2-(carboxymethoxy)-4-fluorobenzoic acid, and 4,4-propanediyldioxydibenzoic acid directly participate in the polyester synthesis reaction to form a stable block polymer) to achieve polyester modification, avoid the compatibility problem caused by doping modification, and make the polyester film performance more uniform and stable.

[0035] 3. The present invention directly melt-extrudes and stretches the modified polyester into a film, which has a simple process and low cost.

[0036] 4. The optical polyester film of the present invention does not require deep processing of release layer and anti-scratch layer, and is environmentally friendly and pollution-free. DETAILED DESCRIPTION

[0037] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0039] Definition: In this application, dicarboxylic acid is a dibasic acid.

[0040] The invention discloses a biaxially oriented optical polyester film, which is co-extruded by using a three-layer structure of A / B / A or A / B / C. The A layer and the C layer contain modified polyester.

[0041] The modified polyester is obtained by copolymerizing a dibasic acid and a diol;

[0042] Specifically, the dibasic acids used are 4-(3,5-dicarboxyphenoxy)phthalic acid, 2-(carboxymethoxy)-4-fluorobenzoic acid, 4,4-propanediyldioxydibenzoic acid, and terephthalic acid.

[0043] Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid component relative to the total dicarboxylic acid component in the modified polyester is X1; the content of 2-(carboxymethoxy)-4-fluorobenzoic acid component relative to the total dicarboxylic acid component is X2; the content of 4,4-propanediyldioxydibenzoic acid component relative to the total dicarboxylic acid component is X3; the content of terephthalic acid component relative to the total dicarboxylic acid component is X4. X1, X2, X3, and X4 satisfy the following relationship:

[0044] 5 mol%≤X1≤15 mol%

[0045] 2 mol%≤X2≤10 mol%

[0046] 3 mol%≤X3≤25 mol%

[0047] 50 mol%≤X4≤90 mol%

[0048] X1+X2+X3+X4=100 mol%.

[0049] Among them, 4-(3,5-dicarboxyphenoxy)phthalic acid, whether the dicarboxyl groups on the same benzene ring or on two benzene rings participate in the reaction, can ensure that the two carboxyl groups are vacant outside. The carboxyl group is a polar group. When used in the production of polyester film, it exists on the surface of the polyester film; when it is bonded with the hydrophilic self-repairing surface, it can "induce" the hydrophilic groups in the self-repairing surface to face outward, so the water contact angle of the self-repairing surface will not be affected after bonding, and it may even increase the hydrophilicity of the self-repairing surface. At the same time, the carboxyl group is highly active, which increases the instability of the modified polyester, and the presence of the phenoxy group has a good stabilizing effect on the polymer material, which can effectively prevent the oxidation and decomposition reactions of the polymer material, and effectively compensate for the instability of the modified polyester caused by the vacant carboxyl group.

[0050] The content of 4-(3,5-dicarboxyphenoxy)phthalic acid component in the modified polyester relative to the total dicarboxylic acid component is 5 mol%≤X1≤15 mol%, preferably 7 mol%≤X1≤12 mol%. If the content is less than 5 mol%, the effect of the modified monomer cannot be exerted, and if the content is greater than 15 mol%, the hydrophilic effect in the self-repairing surface is affected.

[0051] Among them, the methoxy group in 2-(carboxymethoxy)-4-fluorobenzoic acid is a group with high electronegativity and strong electron donor properties. Due to the expansion of the electron cloud of the oxygen atom on the methoxy group and the pushing effect of the electron pair, the methoxy group can increase the steric hindrance of the atom or molecule, change the electron distribution and charge density, and increase the steric hindrance; the methoxy group can also form hydrogen bonds, affect the interaction between molecules, and ensure the stability and transparency of the modified polyester. The fluorine group has a strong polarity, which can also make the hydrophilic group in the self-healing surface face outward.

[0052] The content of 2-(carboxymethoxy)-4-fluorobenzoic acid component in the modified polyester relative to the total dicarboxylic acid component is 2 mol%≤X2≤10 mol%, preferably 3 mol%≤X2≤9 mol%. When the content is less than 2 mol%, the effect of the modified monomer cannot be exerted, and when the content is greater than 10 mol%, the lamination effect of the self-repairing surface is affected.

[0053] Among them, the presence of 4,4-propanediyldioxydibenzoic acid and diphenoxy further ensures the stability of the modified polyester with strong polarity. The content of 4,4-propanediyldioxydibenzoic acid component in the modified polyester relative to the total dicarboxylic acid component is 3 mol%≤X3≤25 mol%, preferably 5 mol%≤X3≤20 mol%. If the content is less than 3 mol%, the role of the modified monomer cannot be exerted, and if the content is greater than 25 mol%, the modified polyester is affected, resulting in changes in the main structure of polyethylene terephthalate.

[0054] In order to be perpendicular to the direction of the polymer chain segment, hydrogen bonds are formed between the three dicarboxylic acid molecules, which provides a carrier, increases the intermolecular force, makes it difficult for the polymer chain segment to creep, and effectively inhibits the formation of orange peel texture on the surface of the polyester film.

[0055] Among them, the presence of terephthalic acid ensures that the entire polyester system remains unchanged.

[0056] In the present invention, several acid monomers interact and coordinate with each other and are indispensable. At the same time, 4-(3,5-dicarboxyphenoxy)phthalic acid, 2-(carboxymethoxy)-4-fluorobenzoic acid, 4,4-propanediyldioxydibenzoic acid and terephthalic acid are designed through appropriate total dicarboxylic acid component content, so that the polyester film has the advantages of not affecting the water contact angle of the PPF self-repairing surface before and after peeling, no orange peel texture, easy peeling, simple process and low cost.

[0057] The modified polyester of the present invention can be prepared by the following method:

[0058] 1. Add the required dibasic acid, diol, catalyst and stabilizer into the polyester reactor in sequence and beat for 15 minutes; introduce nitrogen protection and carry out esterification at 235℃~260℃ and 260KPa for 2.5h~4h.

[0059] The dibasic acid is selected from 4-(3,5-dicarboxyphenoxy)phthalic acid, 2-(carboxymethoxy)-4-fluorobenzoic acid, 4,4-propanediyldioxydibenzoic acid, and terephthalic acid, wherein the content of 4-(3,5-dicarboxyphenoxy)phthalic acid component relative to the total dicarboxylic acid components in the modified polyester is 5 mol%≤X1≤15 mol%, preferably 7 mol%≤X1≤12 mol%; the content of 2-(carboxymethoxy)-4-fluorobenzoic acid component relative to the total dicarboxylic acid components is 2 mol%≤X2≤10 mol%, preferably 3 mol%≤X2≤9 mol%; the content of 4,4-propanediyldioxydibenzoic acid component relative to the total dicarboxylic acid components is 3 mol%≤X3≤25 mol%, preferably 5 mol%≤X3≤20 mol%, and X1+X2+X3+X4=100 mol%.

[0060] The diol is selected from ethylene glycol, propylene glycol, butanediol, 1,4-cyclohexanedimethanol, hexanediol, polyethylene oxide glycol, etc., preferably ethylene glycol.

[0061] The molar ratio of the dibasic acid to the diol is 1:1.21 to 1:1.46.

[0062] The catalyst is selected from antimony, iron, aluminum, germanium, titanium and the like, and the addition amount of ethylene glycol antimony is preferably 80 ppm to 300 ppm.

[0063] The stabilizer is selected from trimethyl phosphate, triethyl phosphate, triphenyl phosphate, tri-n-butyl phosphate, tetrabutyl titanate, tetraethyl titanate, etc., preferably triphenyl phosphate, and the addition amount is 25ppm to 130ppm.

[0064] 2. The end point of esterification is determined according to the amount of water output. After the esterification is complete, vacuum is turned on. The polycondensation reaction is carried out for 3h to 5h at 262°C to 280°C and 25Pa to 70Pa. After spinning, cooling, pelletizing and drying, the modified polyester of the present invention is obtained. The modified polyester has an intrinsic viscosity of 0.58dl / g to 0.68dl / g.

[0065] The optical polyester film of the present invention has a thickness of 19 μm to 150 μm.

[0066] The optical polyester film structure is a three-layer A / B / A, and the thickness ratio of the A layer to the B layer is 1:16 to 1:5.

[0067] The optical polyester film structure is a three-layer A / B / C, the thickness ratio of layer A to layer B is 1:35-1:10, the thickness ratio of layer C to layer B is 1:35-1:10, and the thickness of layer A and layer C can be the same or different.

[0068] The optical polyester film structure is a three-layer structure of A / B / C, and the components of the A layer and the C layer can be the same or different.

[0069] Generally, in order to increase the smoothness of polyester film and improve the winding and slitting performance of polyester film in the prior art, a polyester masterbatch containing micron-sized smooth particles is often added to the surface layer. The viscosity of the polyester masterbatch is 0.62 dl / g, the concentration of the micron-sized smooth particles in the polyester masterbatch is 0.3%, and the particle size is 1.5 μm; the micron-sized smooth particles are selected from silicon dioxide, calcium carbonate, kaolin, barium sulfate, etc., preferably silicon dioxide.

[0070] The optical polyester film is prepared by die co-extrusion, sheet casting, longitudinal stretching, transverse stretching, shaping, pulling and winding.

[0071] The optical polyester film of the present invention can be prepared by the following method:

[0072] 1. Add the prepared modified polyester to the A layer and C layer of the polyester film, add a polyester masterbatch containing micron-sized smooth particles to the surface layer, add a pure polyester resin (usually polyethylene terephthalate without any modification) with a characteristic viscosity of 0.66 dl / g to the B layer, and perform melt extrusion. The viscosity of the polyester masterbatch is 0.62 dl / g, the concentration of silica particles in the polyester masterbatch is 0.3%, and the particle size is 1.5 μm.

[0073] 2. The melt is co-extruded through the die head and cast onto the casting roll to form a three-layer co-extruded casting sheet.

[0074] 3. The cast sheet is longitudinally stretched with a longitudinal stretching ratio of 2.7 to 3.8.

[0075] 4. The longitudinally drawn sheet is stretched transversely with a transverse stretching ratio of 3.3 to 5.6.

[0076] 5. The stretched film is heat-set at a temperature of 220°C to 243°C.

[0077] 6. Then cool, pull and reel.

[0078] The present invention is further described below in conjunction with embodiments, but the implementation and protection scope of the present invention are not limited to these embodiments.

[0079] Example 1

[0080] Preparation of modified polyester:

[0081] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.21, the addition amount of ethylene glycol antimony is 80ppm, and the addition amount of triphenyl phosphate is 25ppm. Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid, 2-(carboxymethoxy)-4-fluorobenzoic acid, 4,4-propanediyldioxydibenzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid components is: X1=5 mol%, X2=2 mol%, X3=1. =3 mol%, X4 = 90 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C ~ 262°C, 265KPa for 2.5 hours; after the esterification is completed, vacuum is turned on, and the polycondensation reaction is carried out at 265°C ~ 282°C, 25Pa for 3 hours. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.58dl / g is obtained.

[0082] The modified polyester of the present invention in layer A and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in the surface layer of the polyester film is 350 ppm, and the pure polyester resin with an intrinsic viscosity of 0.66 dl / g in layer B are added to a corresponding extrusion system, melted at a temperature of 260°C, co-extruded through a die head, and cast onto a casting roll to form a three-layer A / B / A extruded casting sheet; the casting sheet is longitudinally stretched at a longitudinal stretching temperature of 75°C to 87°C and a longitudinal stretching ratio of 3.8; the longitudinally stretched sheet is transversely stretched at a transverse stretching temperature of 108°C to 130°C and a transverse stretching ratio of 5.6; the stretched film is shaped and cooled at a shaping temperature of 220°C; the film is then cooled, pulled, and rolled to obtain an optical polyester film with a thickness of 19 μm, wherein the thickness ratio of layer A to layer B is 1:5.

[0083] Example 2

[0084] Preparation of modified polyester:

[0085] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.3, the addition amount of titanium dioxide is 100ppm, and the addition amount of triphenyl phosphate is 35ppm. Among them, the content rate of each component of the dibasic acid relative to the total dicarboxylic acid component is: X1=7mol%, X2=3mol%, X3= 5 mol%, X4 = 85 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C ~ 262°C, 265KPa for 2.5 hours; after the esterification is completed, vacuumization is turned on, and the condensation reaction is carried out at 265°C ~ 282°C, 35Pa for 3.5 hours. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.60dl / g is obtained.

[0086] The modified polyester of the present invention in layer A and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in the surface layer of the polyester film is 400 ppm, and a pure polyester resin with an intrinsic viscosity of 0.66 dl / g in layer B are added to a corresponding extrusion system, melted at a temperature of 265°C, co-extruded through a die head, and cast onto a casting roll to form a three-layer A / B / A extruded casting sheet; the casting sheet is longitudinally stretched at a longitudinal stretching temperature of 75°C to 87°C and a longitudinal stretching ratio of 3.5; the longitudinally stretched sheet is transversely stretched at a transverse stretching temperature of 108°C to 130°C and a transverse stretching ratio of 5.2; the stretched film is shaped and cooled at a shaping temperature of 225°C; the film is then cooled, pulled, and rolled to obtain an optical polyester film with a thickness of 23 μm, wherein the thickness ratio of layer A to layer B is 3:20.

[0087] Example 3

[0088] Preparation of modified polyester:

[0089] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.33, the addition amount of ethylene glycol antimony is 150ppm, and the addition amount of triphenyl phosphate is 50ppm. Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid, 2-(carboxymethoxy)-4-fluorobenzoic acid, 4,4-propanediyldioxydibenzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid components is: X1=7 mol%, X2=5 mol%, X3=10 mol%, X4=10 mol%, X5=10 mol%, X6=10 mol%, X7=10 mol%, X8=10 mol%, X9=10 mol%, X11=10 mol%, X12=10 mol%, X13=10 mol%, X14=10 mol%, X15=10 mol%, X16=10 mol%, X17=10 mol%, X18=10 mol%, X19=10 mol%, X20=10 mol%, X219=10 mol%, X22 =8 mol%, X4=80 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C~262°C, 265KPa for 3h; after the esterification is completed, vacuum is turned on, and the condensation reaction is carried out at 265°C~282°C, 35Pa for 3.5h. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.61dl / g is obtained.

[0090] The modified polyester of the present invention in layer A and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in the surface layer of the polyester film is 400 ppm, and a pure polyester resin with an intrinsic viscosity of 0.66 dl / g in layer B are added to a corresponding extrusion system, melted at a temperature of 265°C, co-extruded through a die head, and cast onto a casting roll to form a three-layer A / B / A extruded casting sheet; the casting sheet is longitudinally stretched at a longitudinal stretching temperature of 75°C to 87°C and a longitudinal stretching ratio of 3.5; the longitudinally stretched sheet is transversely stretched at a transverse stretching temperature of 108°C to 130°C and a transverse stretching ratio of 5.0; the stretched film is shaped and cooled at a shaping temperature of 230°C; the film is then cooled, pulled, and rolled to obtain an optical polyester film with a thickness of 38 μm, wherein the thickness ratio of layer A to layer B is 3:25.

[0091] Example 4

[0092] Preparation of modified polyester:

[0093] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.35, the addition amount of ethylene glycol antimony is 180ppm, and the addition amount of triphenyl phosphate is 65ppm. Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid, 2-(carboxymethoxy)-4-fluorobenzoic acid, 4,4-propanediyldioxydibenzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid components is: X1=9 mol%, X2=4 mol%, X 3=12 mol %, X4=75 mol %, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236℃~262℃, 265KPa for 3h; after the esterification is completed, vacuum is turned on, and condensation reaction is carried out at 265℃~282℃, 50Pa for 4h, and after silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.64dl / g is obtained.

[0094] The modified polyester of the present invention in layer A and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in the surface layer of the polyester film is 500 ppm, and a pure polyester resin with an intrinsic viscosity of 0.66 dl / g in layer B are added to a corresponding extrusion system, melted at a temperature of 265°C, co-extruded through a die head, and cast onto a casting roll to form a three-layer A / B / A extruded casting sheet; the casting sheet is longitudinally stretched at a longitudinal stretching temperature of 75°C to 87°C and a longitudinal stretching ratio of 3.3; the longitudinally stretched sheet is transversely stretched at a transverse stretching temperature of 108°C to 130°C and a transverse stretching ratio of 4.9; the stretched film is shaped and cooled at a shaping temperature of 232°C; the film is then cooled, pulled, and rolled to obtain an optical polyester film with a thickness of 50 μm, wherein the thickness ratio of layer A to layer B is 1:5.

[0095] Example 5

[0096] Preparation of modified polyester layer A:

[0097] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.35, the addition amount of ethylene glycol antimony is 180ppm, and the addition amount of triethyl phosphate is 65ppm. Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid, 2-(carboxymethoxy)-4-fluorobenzoic acid, 4,4-propanediyldioxydibenzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid components is: X1=9 mol%, X2=4 mol%, X 3=12 mol %, X4=75 mol %, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236℃~262℃, 265KPa for 3h; after the esterification is completed, vacuum is turned on, and condensation reaction is carried out at 265℃~282℃, 50Pa for 4h, and after silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.64dl / g is obtained.

[0098] Preparation of C layer modified polyester:

[0099] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.35, the addition amount of ethylene glycol antimony is 180ppm, and the addition amount of triphenyl phosphate is 65ppm. Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid, 2-(carboxymethoxy)-4-fluorobenzoic acid, 4,4-propanediyldioxydibenzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid components is: X1=8 mol%, X2=6 mol%, X 3=10 mol %, X4=76 mol %, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236℃~262℃, 265KPa for 3h; after the esterification is completed, vacuum is turned on, and condensation reaction is carried out at 265℃~282℃, 55Pa for 4h, and after silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.63dl / g is obtained.

[0100] The modified polyester of the present invention in layer A and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in layer A of the polyester film is 500 ppm, the modified polyester of the present invention in layer C and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in layer C of the polyester film is 500 ppm, and the pure silica with an intrinsic viscosity of 0.66 dl / g in layer B are prepared. The polyester resin is added into the corresponding extrusion system, melted at a temperature of 270°C, co-extruded through a die head, and cast onto a casting roll to form a three-layer A / B / C extruded casting sheet; the casting sheet is longitudinally stretched at a longitudinal stretching temperature of 75°C to 87°C and a longitudinal stretching ratio of 3.3; the longitudinally stretched sheet is transversely stretched at a transverse stretching temperature of 108°C to 130°C and a transverse stretching ratio of 4.9; the stretched film is shaped and cooled at a shaping temperature of 232°C; the film is then cooled, pulled and rolled to obtain an optical polyester film with a thickness of 50 μm, wherein the thickness ratio of the A layer to the B layer is 1:10, and the thickness ratio of the C layer to the B layer is 1:10.

[0101] Example 6

[0102] Preparation of modified polyester:

[0103] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.4, the addition amount of ethylene glycol antimony is 200ppm, and the addition amount of triphenyl phosphate is 90ppm. Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid, 2-(carboxymethoxy)-4-fluorobenzoic acid, 4,4-propanediyldioxydibenzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid components is: X1=10mol%, X2=7mol%, X3=10mol%, X4=10mol%, X5=10mol%, X6=10mol%, X7=10mol%, X8=10mol%, X9=10mol%, X10=10mol%, X11=10mol%, X12=10mol%, X13=10mol%, X14=10mol%, X15=10mol%, X16=10mol%, X17=10mol%, X18=10mol%, X19=10mol%, X20=10mol%, X21=10mol%, X22=10mol%, X3 =13 mol%, X4=70 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C~262°C, 265KPa for 3h; after the esterification is completed, vacuum is turned on, and the polycondensation reaction is carried out at 265°C~282°C, 65Pa for 4.5h. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.66dl / g is obtained.

[0104] The modified polyester of the present invention in layer A and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in the surface layer of the polyester film is 500 ppm, and the pure polyester resin with an intrinsic viscosity of 0.66 dl / g in layer B are added to the corresponding extrusion system, melted at a temperature of 275° C., co-extruded through a die head, and cast onto a casting sheet. On the roller, a three-layer A / B / A extruded cast sheet is formed; the cast sheet is longitudinally stretched, the longitudinal stretching temperature is 75°C ~ 87°C, and the longitudinal stretching ratio is 3.3; the longitudinally stretched sheet is transversely stretched, the transverse stretching temperature is 108°C ~ 130°C, and the transverse stretching ratio is 4.6; the stretched film is shaped and cooled, and the shaping temperature is 235°C; then the film is cooled, pulled, and rolled to obtain an optical polyester film with a thickness of 75μm, wherein the thickness ratio of layer A to layer B is 9:100.

[0105] Example 7

[0106] Preparation of modified polyester:

[0107] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.4, the addition amount of ethylene glycol antimony is 200ppm, and the addition amount of triphenyl phosphate is 100ppm. Among them, the content rate of each component of the dibasic acid relative to the total dicarboxylic acid component is: X1=10mol%, X2=8mol%, X3= 14 mol%, X4 = 68 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C ~ 262°C, 265KPa for 3.5 hours; after the esterification is completed, vacuumization is turned on, and condensation reaction is carried out at 265°C ~ 282°C, 60Pa for 4.5 hours. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.66dl / g is obtained.

[0108] The modified polyester of the present invention in layer A and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in the surface layer of the polyester film is 580 ppm, and the pure polyester resin with an intrinsic viscosity of 0.66 dl / g in layer B are added to the corresponding extrusion system, melted at a temperature of 275° C., co-extruded through a die head, and cast onto a casting sheet. On the roller, a three-layer A / B / A extruded cast sheet is formed; the cast sheet is longitudinally stretched, the longitudinal stretching temperature is 75°C ~ 87°C, and the longitudinal stretching ratio is 3.2; the longitudinally stretched sheet is transversely stretched, the transverse stretching temperature is 108°C ~ 130°C, and the transverse stretching ratio is 4.3; the stretched film is shaped and cooled, and the shaping temperature is 235°C; then the film is cooled, pulled, and rolled to obtain an optical polyester film with a thickness of 100μm, wherein the thickness ratio of layer A to layer B is 1:10.

[0109] Example 8

[0110] Preparation of modified polyester:

[0111] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.4, the addition amount of ethylene glycol antimony is 200ppm, and the addition amount of triphenyl phosphate is 100ppm. Among them, the content rate of each component of the dibasic acid relative to the total dicarboxylic acid component is: X1=8mol%, X2=10mol%, X3= 16 mol%, X4 = 66 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C ~ 262°C, 265KPa for 3.5 hours; after the esterification is completed, vacuum is turned on, and the condensation reaction is carried out at 265°C ~ 282°C, 60Pa for 4.5 hours. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.66dl / g is obtained.

[0112] The modified polyester of the present invention of layer A and layer C and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in the surface layer of the polyester film is 580 ppm, and a pure polyester resin with an intrinsic viscosity of 0.66 dl / g of layer B are added to a corresponding extrusion system, melted at a temperature of 275° C., co-extruded through a die head, and cast onto a casting roll to form a three-layer film. The film is formed by extruding a cast sheet with layers A / B / C; the cast sheet is longitudinally stretched at a temperature of 75°C to 87°C and a longitudinal stretch ratio of 3.2; the longitudinally stretched sheet is transversely stretched at a temperature of 108°C to 130°C and a transverse stretch ratio of 4.3; the stretched film is shaped and cooled at a temperature of 235°C; the film is then cooled, pulled and rolled to obtain an optical polyester film with a thickness of 100 μm, wherein the thickness ratio of layer A to layer B is 1:16, and the thickness ratio of layer C to layer B is 1:25.

[0113] Example 9

[0114] Preparation of modified polyester:

[0115] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.43, the addition amount of ethylene glycol antimony is 250ppm, and the addition amount of triphenyl phosphate is 110ppm. Among them, the content rate of each component of the dibasic acid relative to the total dicarboxylic acid component is: X1=12mol%, X2=7mol%, X3=18 mol%, X4=63 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out for 3 hours at 236°C~262°C and 265KPa; after the esterification is completed, vacuumization is turned on, and condensation reaction is carried out for 4 hours at 265°C~282°C and 55Pa. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.67dl / g is obtained.

[0116] The modified polyester of the present invention in layer A and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in the surface layer of the polyester film is 650 ppm, and the pure polyester resin with an intrinsic viscosity of 0.66 dl / g in layer B are added to the corresponding extrusion system, melted at a temperature of 280° C., co-extruded through a die head, and cast onto a casting sheet. On the roller, a three-layer A / B / A extruded cast sheet is formed; the cast sheet is longitudinally stretched, the longitudinal stretching temperature is 75°C ~ 87°C, and the longitudinal stretching ratio is 3.0; the longitudinally stretched sheet is transversely stretched, the transverse stretching temperature is 108°C ~ 130°C, and the transverse stretching ratio is 3.8; the stretched film is shaped and cooled, and the shaping temperature is 240°C; then the film is cooled, pulled, and rolled to obtain an optical polyester film with a thickness of 100μm, wherein the thickness ratio of layer A to layer B is 3:25.

[0117] Example 10

[0118] Preparation of modified polyester:

[0119] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.46, the addition amount of ethylene glycol antimony is 300ppm, and the addition amount of triphenyl phosphate is 130ppm. Among them, the content rate of each component of the dibasic acid relative to the total dicarboxylic acid component is: X1=12mol%, X2=9mol%, X3=20 mol%, X4=59 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out for 4 hours at 236°C~262°C and 265KPa; after the esterification is completed, vacuumization is turned on, and condensation reaction is carried out for 5 hours at 265°C~282°C and 55Pa. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.68dl / g is obtained.

[0120] The modified polyester of the present invention in layer A and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in the surface layer of the polyester film is 750 ppm, and the pure polyester resin with an intrinsic viscosity of 0.66 dl / g in layer B are added to the corresponding extrusion system, melted at a temperature of 280° C., co-extruded through a die head, and cast onto a casting sheet. On the roller, a three-layer A / B / A extruded cast sheet is formed; the cast sheet is longitudinally stretched, the longitudinal stretching temperature is 75°C ~ 87°C, and the longitudinal stretching ratio is 2.7; the longitudinally stretched sheet is transversely stretched, the transverse stretching temperature is 108°C ~ 130°C, and the transverse stretching ratio is 3.3; the stretched film is shaped and cooled, and the shaping temperature is 243°C; then the film is cooled, pulled, and rolled to obtain an optical polyester film with a thickness of 125μm, wherein the thickness ratio of layer A to layer B is 1:16.

[0121] Embodiment 11

[0122] Preparation of modified polyester:

[0123] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.46, the addition amount of ethylene glycol antimony is 300ppm, and the addition amount of triphenyl phosphate is 130ppm. Among them, the content rate of each component of the dibasic acid relative to the total dicarboxylic acid component is: X1=15mol%, X2=10mol%, X3=25 mol%, X4=50 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out for 4 hours at 236°C~262°C and 265KPa; after the esterification is completed, vacuumization is turned on, and condensation reaction is carried out for 5 hours at 265°C~282°C and 50Pa. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.68dl / g is obtained.

[0124] The modified polyester of the present invention of layer A and layer C and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in the surface layer of the polyester film is 650 ppm, and a pure polyester resin with an intrinsic viscosity of 0.66 dl / g of layer B are added to a corresponding extrusion system, melted at a temperature of 280° C., co-extruded through a die head, and cast onto a casting roll to form a three-layer film. The invention discloses a method for preparing an optical polyester film having layers A / B / C and extruding the cast sheet; longitudinally stretching the cast sheet at a longitudinal stretching temperature of 75°C to 87°C and a longitudinal stretching ratio of 2.7; transversely stretching the longitudinally stretched sheet at a transverse stretching temperature of 108°C to 130°C and a transverse stretching ratio of 3.3; shaping and cooling the stretched film at a shaping temperature of 243°C; then cooling, pulling and winding the film to obtain an optical polyester film with a thickness of 150 μm, wherein the thickness ratio of layer A to layer B is 1:35, and the thickness ratio of layer C to layer B is 1:35.

[0125] Example 12

[0126] Preparation of modified polyester layer A:

[0127] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.46, the addition amount of ethylene glycol antimony is 300ppm, and the addition amount of triphenyl phosphate is 130ppm. Among them, the content rate of each component of the dibasic acid relative to the total dicarboxylic acid component is: X1=15mol%, X2=10mol%, X3=25 mol%, X4=50 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out for 4 hours at 236°C~262°C and 265KPa; after the esterification is completed, vacuumization is turned on, and condensation reaction is carried out for 5 hours at 265°C~282°C and 50Pa. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.68dl / g is obtained.

[0128] Preparation of C layer modified polyester:

[0129] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.46, the addition amount of ethylene glycol antimony is 300ppm, and the addition amount of triphenyl phosphate is 130ppm. Among them, the content rate of each component of the dibasic acid relative to the total dicarboxylic acid component is: X1=15mol%, X2=8mol%, X3=17 mol%, X4=60 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out for 4 hours at 236°C~262°C and 265KPa; after the esterification is completed, vacuumization is turned on, and condensation reaction is carried out for 5 hours at 265°C~282°C and 50Pa. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.68dl / g is obtained.

[0130] The modified polyester of the present invention in layer A and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in layer A of the polyester film is 650 ppm, the modified polyester of the present invention in layer C and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in layer C of the polyester film is 650 ppm, and the pure polyester of layer B with an intrinsic viscosity of 0.66 dl / g The polyester resin is added into the corresponding extrusion system, melted at a temperature of 275°C, co-extruded through a die head, and cast onto a casting roll to form a three-layer A / B / C extruded casting sheet; the casting sheet is longitudinally stretched at a longitudinal stretching temperature of 75°C to 87°C and a longitudinal stretching ratio of 2.7; the longitudinally stretched sheet is transversely stretched at a transverse stretching temperature of 108°C to 130°C and a transverse stretching ratio of 3.3; the stretched film is shaped and cooled at a shaping temperature of 240°C; the film is then cooled, pulled and rolled to obtain an optical polyester film with a thickness of 50 μm, wherein the thickness ratio of layer A to layer B is 1:25, and the thickness ratio of layer C to layer B is 1:35.

[0131] Comparative Example 1

[0132] A layer of pure polyester resin with an intrinsic viscosity of 0.641 dl / g and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in the surface layer of the polyester film is 400 ppm, and a layer of pure polyester resin with an intrinsic viscosity of 0.66 dl / g are added to the corresponding extrusion system, melted at a temperature of 265°C, and passed through a die head. Co-extrude and cast onto a casting roll to form a three-layer A / B / A extruded casting sheet; the casting sheet is longitudinally stretched at a temperature of 75°C to 87°C and a longitudinal stretch ratio of 3.5; the longitudinally stretched sheet is transversely stretched at a temperature of 108°C to 130°C and a transverse stretch ratio of 5.0; the stretched film is shaped and cooled at a shaping temperature of 230°C; the film is then cooled, pulled and rolled to obtain an optical polyester film with a thickness of 38 μm, wherein the thickness ratio of layer A to layer B is 3:25.

[0133] Comparative Example 2

[0134] A layer of pure polyester resin with an intrinsic viscosity of 0.64 dl / g and a smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in the surface layer of the polyester film is 500 ppm, and a layer of pure polyester resin with an intrinsic viscosity of 0.66 dl / g are added to the corresponding extrusion system, melted at a temperature of 265°C, and passed through a die head. Co-extrude and cast onto a casting roll to form a three-layer A / B / A extruded casting sheet; the casting sheet is longitudinally stretched at a temperature of 75°C to 87°C and a longitudinal stretch ratio of 3.3; the longitudinally stretched sheet is transversely stretched at a temperature of 108°C to 130°C and a transverse stretch ratio of 4.9; the stretched film is shaped and cooled at a shaping temperature of 232°C; the film is then cooled, pulled and rolled to obtain an optical polyester film with a thickness of 50 μm, wherein the thickness ratio of layer A to layer B is 1:5.

[0135] Comparative Example 3

[0136] The pure polyester resin with an intrinsic viscosity of 0.646 dl / g for the A and C layers and the smooth polyester masterbatch containing silica with an average particle size of 1.5 μm, a concentration of 0.3%, and an intrinsic viscosity of 0.62 dl / g, wherein the content of silica particles with an average particle size of 1.5 μm in the surface layer of the polyester film is 580 ppm, and the pure polyester resin with an intrinsic viscosity of 0.66 dl / g for the B layer are added to the corresponding extrusion system, melted at a temperature of 275°C, co-extruded through a die head, and cast onto a casting On the sheet roller, a three-layer A / B / C extruded cast sheet is formed; the cast sheet is longitudinally stretched, the longitudinal stretching temperature is 75°C to 87°C, and the longitudinal stretching ratio is 3.2; the longitudinally stretched sheet is transversely stretched, the transverse stretching temperature is 108°C to 130°C, and the transverse stretching ratio is 4.3; the stretched film is shaped and cooled, and the shaping temperature is 235°C; then the film is cooled, pulled, and rolled to obtain an optical polyester film with a thickness of 100 μm, wherein the thickness ratio of layer A to layer B is 1:16, and the thickness ratio of layer C to layer B is 1:25.

[0137] Table 1 Specific implementation effects

[0138]

[0139] Note: When the interlayer structure of the optical polyester film of the present invention is A / B / C, when it is bonded to the self-repairing surface, it includes but is not limited to the A surface.

[0140] Thickness test method: GB / T 33399-2016.

[0141] Water contact angle test method: GB / T 30693-2014. Using the same hydrophilic self-repairing layer formula and the same production process, after the self-repairing layer is cured and cross-linked in the oven, take the sample without laminating film from the self-repairing surface, and after aging in a 40°C environment for 72 hours, test the water contact angle of the self-repairing surface before peeling, and record it as the water contact angle of the self-repairing surface before peeling; using the same formula and process as above, after the self-repairing layer is cured and cross-linked in the oven, use 0.3kg laminating pressure to cold-laminate the self-repairing surface with the optical polyester film, and after aging in a 40°C environment for 72 hours, tear off the optical polyester film, and test the water contact angle of the self-repairing surface, and record it as the water contact angle of the self-repairing surface before peeling.

[0142] Cellulite evaluation method:

[0143] Take an optical polyester film with a width of 1 meter and a length of 1 meter. Use a fluorescent lamp or a strong light lamp with an angle of about 45° between the light and the film surface. The distance between the light spot and the human eye and the film is about 30 cm. Observe the film in a reflective manner. Visually inspect the film surface. If the film surface is bright and smooth, record "◎"; if the film surface is uneven like "orange peel", record "×".

[0144] By comparing Example 3 with Comparative Example 1, Example 4 with Comparative Example 2, and Example 8 with Comparative Example 3, it can be seen that under the same conditions of polyester film thickness, film making process, surface silica addition concentration, etc., the optical polyester film of the present invention has no effect on the water contact angle of the self-repairing surface before and after peeling, and the orange peel texture is significantly better than that of ordinary polyester film.

[0145] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0146] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A biaxially oriented optical polyester film, co-extruded with a three-layer structure of A / B / A or A / B / C, characterized in that: Layers A and C contain modified polyester; The modified polyester is obtained by copolymerizing a dibasic acid and a diol; Wherein, the dibasic acid is 4-(3,5-dicarboxyphenoxy)phthalic acid, 2-(carboxymethoxy)-4-fluorobenzoic acid, 4,4-propanediyldioxydibenzoic acid and terephthalic acid; Definition: X1 is the content ratio of 4-(3,5-dicarboxyphenoxy)phthalic acid component relative to the total dicarboxylic acid components in the modified polyester; X2 is the content ratio of 2-(carboxymethoxy)-4-fluorobenzoic acid component relative to the total dicarboxylic acid components in the modified polyester; X3 is the content ratio of 4,4-propanediyldioxydibenzoic acid component relative to the total dicarboxylic acid components in the modified polyester; X4 is the content of terephthalic acid component relative to the total dicarboxylic acid components in the modified polyester; Among them, X1, X2, X3, and X4 satisfy the following relationship: 5 mol%≤X1≤15 mol% 2 mol%≤X2≤10 mol% 3 mol%≤X3≤25 mol% 50 mol%≤X4≤90 mol% X1+X2+X3+X4=100 mol%.

2. A biaxially oriented optical polyester film according to claim 1, characterized in that: The content of the 4-(3,5-dicarboxyphenoxy)phthalic acid component in the modified polyester relative to the total dicarboxylic acid components is 7 mol %≤X1≤12 mol %.

3. The biaxially oriented optical polyester film according to claim 1, characterized in that: The content of the 2-(carboxymethoxy)-4-fluorobenzoic acid component in the modified polyester relative to the total dicarboxylic acid components is 3 mol % ≤ X2 ≤ 9 mol %.

4. The biaxially oriented optical polyester film according to claim 1, characterized in that: The content of the 4,4-propanediyldioxydibenzoic acid component in the modified polyester relative to the total dicarboxylic acid components is 5 mol % ≤ X3 ≤ 20 mol %.

5. The biaxially oriented optical polyester film according to claim 1, characterized in that: The diol is selected from one of ethylene glycol, propylene glycol, butanediol, 1,4-cyclohexanedimethanol, hexanediol, polyethylene oxide glycol or multiple thereof in any molar ratio; the molar ratio of the dibasic acid to the diol is 1:1.21 to 1:1.

46.

6. The biaxially oriented optical polyester film according to claim 1, characterized in that: The dibasic acid and the diol are copolymerized under a catalyst, and the catalyst is selected from antimony, iron, aluminum, germanium or titanium catalysts, and the addition amount is 80ppm to 300ppm.

7. The biaxially oriented optical polyester film according to claim 1, characterized in that: The dibasic acid and the diol are copolymerized in the presence of a stabilizer, the stabilizer being selected from trimethyl phosphate, triethyl phosphate, triphenyl phosphate, tri-n-butyl phosphate, tetrabutyl titanate, or tetraethyl titanate; the addition amount is 25ppm to 130ppm.

8. The biaxially oriented optical polyester film according to claim 1, characterized in that: The optical polyester film has a thickness of 19 μm to 150 μm.

9. The biaxially oriented optical polyester film according to claim 1, characterized in that: The biaxially oriented optical polyester film has a three-layer structure of A / B / A, and the thickness ratio of the A layer to the B layer is 1:16 to 1:

5.

10. The biaxially oriented optical polyester film according to claim 1, characterized in that The optical polyester film structure is a three-layer A / B / C, the thickness ratio of layer A to layer B is 1:35-1:10, the thickness ratio of layer C to layer B is 1:35-1:10, and the thickness of layer A and layer C can be the same or different.

Citation Information

Patent Citations

  • Special polyester film with high barrier property and preparation method thereof

    CN117183529A

  • Optical film, polarizing plate and liquid crystal display device

    JP2006328298A

  • Laminated film for transfer foil

    JP2007076026A